Inducing expertise effects in clinical case recall. - Wimmers PF; Schmidt HG; Verkoeijen PP; van de Wiel MWJ (Medical Education, 2005)
BACKGROUND: This study was directed at illuminating a well known phenomenon in the medical expertise literature, the 'intermediate effect' in clinical case recall. This robust phenomenon consists of the finding that medical students of intermediate levels of expertise outperform both experts and novices in clinical case recall after diagnosing cases. It deals in particular with the findings of OME researchers who have reported a monotonically increasing recall with level of expertise. PURPOSE: To address possible causes for this anomaly in medical expertise and to experimentally demonstrate how data elaboration can cause expertise effects in clinical case recall. METHOD: Expert nephrologists, intermediate level students and novices were presented with 6 medical cases under 3 different conditions: laboratory data cases without special instructions, laboratory data cases with instructions to elaborate, and cases with laboratory data and a relevant clinical context. RESULTS: Only when participants were required to elaborate on each of the information units presented to them did case recall show an expertise effect. If laboratory data are framed within the context of a patient's history and physical examination data, the 'intermediate effect' appears. CONCLUSIONS: The instructions used in the elaboration condition seem to have induced a deeper, more detailed, analysis of the patient case. It is therefore interesting to note that these instructions only affected the recall of the experts and had no effect on the novices' or intermediates' recall. We might conclude from this that expertise effects in clinical case recall are only produced when the normal processing of patient information is disrupted.